Knowledge regarding rabies and its prevention among first year medical college students, Mandya - Manjunath, M.; Manuja, L. M.; Harish, B. R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Rabies is a zoonotic disease that is caused by a virus and is always fatal which can be prevented by timely and appropriate post exposure prophylaxis. The large number of deaths due to rabies can be attributed to the fact that in spite of availability of effective vaccination against rabies, people are unaware of various aspects of rabies and its prevention. Hence this study was conducted to assess the knowledge regarding rabies and its prevention among first year medical students. Methods: This descriptive cross sectional study was conducted among first year medical students of Mandya Institute of Medical Sciences, Mandya. The data was collected using pretested semi-structured questionnaire and analysed using descriptive statistics. Results: Of the total 80 students who were included, 90.0% knew that rabies is a disease caused by a virus. All of them knew that dogs transmit rabies. 96.3% were aware of the mode of transmission. 30.0% answered that rabies can be transmitted by scratch. 25% had the wrong perception that rabid person can present with epileptic features. 28.8% had given correct answer regarding the number of doses of vaccination. 86.3% knew that rabies can be prevented by vaccinating animal. Conclusions: Majority of the students had incomplete knowledge about rabies and its cause and mode of transmission and unaware of post exposure prophylaxis.